1998
DOI: 10.1029/98wr01471
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of size and distance of travel of unconstrained particles in interrill flow

Abstract: Abstract. The travel distances of particles ranging in size from 2.88 mm to 10.63 mm were investigated in !.?•.boratory simulations of interrill overland flow. Using travel distances scaled for differences,: among the experiments in flow and rainfall energy, a relationship between distance traveled and particle size is obtained that shows a steep reduction in travel distance with increase in particle size. Travel distance is the outcome of two probabilities: that of moving and that of coming to rest. In interr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Studies have shown that soil loss would occur due to the interception of the plant residues and roots as well as the aggradation of billabongs, ditches, ponds, reservoirs, weirs, and dams in the process of transport (Parsons and Stromberg 1998). To this end, the SDR was introduced and used to explain the spatial and temporal heterogeneity of sediment transport processes and their interactions with rainfall and catchment characteristics within the watershed (Walling 1983;Wang et al 2008).…”
Section: Determination Of the Sediment Delivery Ratiomentioning
confidence: 99%
“…Studies have shown that soil loss would occur due to the interception of the plant residues and roots as well as the aggradation of billabongs, ditches, ponds, reservoirs, weirs, and dams in the process of transport (Parsons and Stromberg 1998). To this end, the SDR was introduced and used to explain the spatial and temporal heterogeneity of sediment transport processes and their interactions with rainfall and catchment characteristics within the watershed (Walling 1983;Wang et al 2008).…”
Section: Determination Of the Sediment Delivery Ratiomentioning
confidence: 99%
“…Future studies should consider how the road smoothness affects the relationship of heavy metals with different chemical fractions between RDS and washoff particles. In addition, all results of washoff particles in this study were based on simulated rainfall experiments; therefore, the findings presented herein should be verified based on natural rainfall in future studies [41].…”
Section: Tablementioning
confidence: 65%
“…Torri et al (1987) suggested that this function is a negative exponential of flow depth to a power. The median travel distance of particles in shallow flows can be considered to be a non-linear function of rainfall energy and flow energy as well as particle mass (Parsons & Stromberg, 1998). On a planar, uniform slope with a uniform infiltration rate and uniform roughness, flow hydraulics can be considered to be simple functions of distance downslope (discharge increases linearly, so that depth increases with x 2/3 , flow velocity with x 1/3 and flow energy with x 5/3 ).…”
Section: Process-based Scaling In Simple Conditionsmentioning
confidence: 99%
“…Wainwright et al (2001) relaxed the assumption that all particles travel the same distance under the same flow conditions. It has long been recognized that particles travel a range of different distances as a result of flow variability (especially turbulent bursts where transitional or turbulent flows occur), microtopographic variations and other factors (Wainwright & Thornes, 1991;Hassan et al, 1992;Parsons & Stromberg, 1998). Travel distance of particles can thus be considered to follow a distribution function, with individual particles moving different distances with a given probabilistic form.…”
Section: Process-based Scaling In Simple Conditionsmentioning
confidence: 99%